A Social-Ecological Approach to Addressing Emotional and Behavioral Problems in Schools: Focusing on Group Processes and Social Dynamics. (March 2018) - Trach, Jessica; Lee, Matthew; Hymel, Shelley
A substantial body of evidence verifies that social-emotional learning (SEL) can be effectively taught in schools and can reduce the prevalence and impact of emotional and behavioral problems (EBP) among children and youth. Although the positive effects of SEL on individual student's emotional, behavioral, and academic outcomes have been investigated in some detail in recent years, most studies have focused on evaluating programs aimed at directly training social and emotional competencies with a focus on the individual. Far less is known about the role of interpersonal group dynamics and systems functioning at the levels of the peer group, classroom, and school community. Drawing on Bronfenbrenner's ecological systems theory and Harris's group socialization theory, this article reviews the literature on SEL and group dynamics to identify the ways in which existing SEL frameworks already encapsulate social group processes that contribute to the promotion of positive social-emotional development of children and youth. The goals of this contribution are twofold: (a) to document how EBP can be attenuated by addressing group-level processes that already exist within SEL practices and (b) to provide educators with specific SEL strategies to address group dynamics in their classrooms to optimize outcomes for all students, including students with EBP.